(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
There is evidence linking physical fitness to an athlete's ability to compete. Physical fitness consists of both skill- and health-related components. Athletes' competitive ability is closely linked to their level of physical fitness, whether it is high or low. Furthermore, developing a sense of physical fitness is heavily dependent on the early teenage stage. More focus should be placed on providing young racquet game players with physical fitness training.The aim of the study was to investigate the effects of a 12-week Functional Training (FT) Programme on agility, and Speed in male tennis and Badminton players. Twenty-eight participants (age: 15.8 ± 0.2 years) were randomly divided into a plyometric group (PG; n = 14) or a control group (CG; n = 14). Significant (group × time) interaction was noted for change of direction (COD) [Modified agility T-test (T-half)], three jumping tests [squat jump (SJ), countermovement jump (CMJ) and standing long jump (SLJ)], repeated sprint ability (RSA), muscular strength (1-RM bench press and 1-RM half squat) and muscular power (force-velocity test for both upper and lower limb). a repeated ANOVA technique was employed, with a level of significance of 0.05.